(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe study-defined treatment continuation, overall survival (OS), and factors associated with mortality among cancer patients participating in the Vietnam Patient Assistance Program (VPAP) at Military Hospital 175. Subjects and methods: This single-center retrospective cohort study included 191 adults receiving Pembrolizumab through VPAP. Treatment continuation was operationally defined as receipt of ≥ 80% of the planned Pembrolizumab cycles. OS was measured from treatment initiation within VPAP to death from any cause; patients alive were censored at their last follow-up. Survival was estimated using Kaplan-Meier methods, and mortality-associated factors were analyzed using Cox regression. Results: The median age was 62 years, and 71.7% were male. Overall, 79.6% met the study-defined treatment-continuation criterion, and median OS was 8 months. In the multivariable Cox model, ECOG performance status ≥ 2 (adjusted HR 11.82, 95% CI: 5.84-23.90; p < 0.001) and age ≥ 65 years (adjusted HR 1.71, 95% CI: 1.10-2.67; p = 0.018) were associated with higher mortality. The combination-chemotherapy group had a lower adjusted hazard of death; this observational association may remain affected by confounding by indication. Conclusions: In this cohort, 79.6% met the operational treatment-continuation criterion. Poor ECOG performance status and older age were independently associated with shorter survival. Regimen-group findings should not be interpreted as causal treatment-effect estimates.